Lenvatinib Plus Programmed Cell Death Protein-1 Inhibitor Beyond First-Line Systemic Therapy in Refractory Advanced Biliary Tract Cancer: A Real-World Retrospective Study in China - Shi, Changying; Li, Yulong; Yang, Cheng; Qiao, Liang; Tang, Liukang; Zheng, Yuting; Chen, Xue; Qian, Youwen; Yang, Jiamei; Wu, Dong; Xie, Feng (Frontiers in Immunology, 2022)
Background Currently, no second-line systemic treatment regimen has been recommended in advanced biliary tract cancer (BTC). Cumulative clinical evidence showed that systemic treatment with tyrosine kinase inhibitors (TKIs) in combination with immunotherapy may shed light on the dim clinical outcome in advanced BTC. Objective The aim of this study is to evaluate the anticancer efficacy of lenvatinib plus programmed cell death protein-1 (PD-1) antibody in patients with BTC who progressed after first-line cisplatin/gemcitabine (CisGem) chemotherapy. Methods Patients with advanced BTCs who progressed after CisGem were recruited. A combination regimen of lenvatinib (8/12 mg daily) plus PD-1 antibody (200/240 mg injection every 3 weeks) was prescribed. Clinicopathological information and therapeutic outcome, including tumor subtypes, biomarkers, treatment duration, adverse events (AE), progression-free survival (PFS), and overall survival (OS), were recorded and estimated. Results A total of 351 patients with BTCs were reviewed and 74 were recruited eventually: 35 had intrahepatic cholangiocarcinoma (47.3%), 4 had extrahepatic cholangiocarcinoma (5.4%), and 35 had gallbladder cancer (47.3%). The median administered cycles of PD-1 antibody were 6.43 (95% CI: 5.83–7.04) cycles, and the median duration of lenvatinib medication was 21.0 weeks (95% CI: 18.04–23.93). Twenty-eight patients (37.83%) experienced detectable objective response per RECIST1.1 within a median follow-up duration of 15.0 months. The objective response rate (ORR) was 20.27% (95% CI: 10.89%–29.65%), and the disease control rate (DCR) was 71.62% (95% CI: 61.11%–82.14%). The median PFS and OS were 4.0 months (95% CI: 3.5–5.0) and 9.50 months (95% CI: 9.0–11.0), respectively. Seventy-three patients (98.64%) reported AEs and 39 (52.70%) experienced ≥grade 3 AEs. In subgroup analyses, tumoral PD-L1 expression ≥50% and tumor mutation burden (TMB) ≥2.5 Muts/Mb were associated with prolonged PFS. Conclusion Lenvatinib plus PD-1 antibody treatment shows an active trend towards improving survival in patients with advanced BTCs after failure with CisGem chemotherapy. The treatment-related AEs are worthy of attention and are manageable.